2018
DOI: 10.1007/s12105-018-0944-0
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Papillary Adenocarcinoma as a Second Head and Neck Malignancy

Abstract: Nasopharyngeal adenocarcinomas are rare tumours, and include neoplasms arising from the nasopharyngeal surface epithelium as well as those of minor salivary gland origin, each of which is distinct from the other. The former encompasses nasopharyngeal papillary adenocarcinoma (NPAC), also known as low grade NPAC and thyroid-like NPAC, an extremely unusual malignancy bearing histomorphological similarity to papillary thyroid carcinoma, and displaying indolent clinical behaviour. We report the case of a 41-year-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…NKC constituted about 91.2% (55.9% WHO type III and 35.3% WHO type II), and 5.9% of NPC patients had squamous cell carcinoma (SCC) (WHO type I) in this study, which was comparable to the previous studies, where they reported higher occurrence rates of NKUC followed by NKDC and lower rates of SCC [58,[60][61][62]. One patient was diagnosed as papillary variant, nasopharyngeal adenocarcinomas (NACs), which is a rare tumor accounting for less than 0.5% of nasopharyngeal malignancies and can occur in up to 10% of NPC cases in the endemic areas [63,64]. The vast majority of NPC patients in this study had locally advanced NPC (stage IV and stage III).…”
Section: Discussionsupporting
confidence: 88%
“…NKC constituted about 91.2% (55.9% WHO type III and 35.3% WHO type II), and 5.9% of NPC patients had squamous cell carcinoma (SCC) (WHO type I) in this study, which was comparable to the previous studies, where they reported higher occurrence rates of NKUC followed by NKDC and lower rates of SCC [58,[60][61][62]. One patient was diagnosed as papillary variant, nasopharyngeal adenocarcinomas (NACs), which is a rare tumor accounting for less than 0.5% of nasopharyngeal malignancies and can occur in up to 10% of NPC cases in the endemic areas [63,64]. The vast majority of NPC patients in this study had locally advanced NPC (stage IV and stage III).…”
Section: Discussionsupporting
confidence: 88%
“…These features are very similar to thyroid papillary adenocarcinoma. In some previously reported cases, the transition from the normal surface respiratory epithelium to tumor cells was identified, [ 2 , 6 – 8 ] all of which were also observed in the present case.…”
Section: Discussionsupporting
confidence: 85%
“…[ 23 ] However, the role of adjuvant radiotherapy is not established as these well-differentiated tumors respond poorly to radiation. [ 6 ] In our case, because the surgical margin was negative, and the patient was young, he did not receive adjuvant radiation therapy or chemotherapy. The patient has remained free of local recurrence and distant metastasis during the 3.5-year postoperative follow-up.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, it was suggested that TL-LGNPPA has an excellent prognosis and that local invasion or distant metastasis of TL-LGNPPA was extremely rare. Some studies have reported the local extension of LGNPPA into the sphenoid sinus (28) or parapharyngeal space (29); however, an immunohistochemical study was negative for TTF-1 in these two cases of LGNPPA. TL-LGNPPA might tend to grow more slowly than LGNPPA without the expression of TTF-1, and the frequency of local invasion might differ from that in LGNPPA without the expression of TTF-1.…”
Section: Discussionmentioning
confidence: 71%